The Renin-Angiotensin System Involvement in Cisplatin-Induced Nephrotoxicity: An Overview of Physiological and Pathological Mechanisms—A Systematic Review - Aryan Vakilian; Sina Mohammadi; Fatemeh Shokri; Maryam Maleki; Maryam Kheiry; Amin Kheiri (International Journal of Nephrology)
Cisplatin (CDDP) is a highly potent chemotherapy drug. But its nephrotoxicity poses a significant limitation to its use. The renin-angiotensin system (RAS) has been proposed to play a role in drug-induced nephrotoxicity. This systematic review (SR) sought to identify the link between CDDP-induced nephrotoxicity and the RAS pathway. In this SR, relevant keywords were employed to explore databases such as PubMed (MEDLINE), Scopus (Elsevier), and Institute for Scientific Information (ISI) Web of Science up to October 2023. Nine studies were selected based on predefined inclusion/exclusion criteria. The findings support the involvement of the RAS in the CDDP-induced nephrotoxicity model, along with the activation of inflammatory mediators, lipid peroxidation, and changes in markers of kidney tissue damage. Furthermore, physiology and pathology of RAS-related interventions in CDDP-induced nephrotoxicity models have involved the factors such as human organic cation transporter 2 (hOCT2), organic anion transporting polypeptides 1B1 (OATP1B1) and 1B3, kallikrein-kinin system, and bradykinin receptors. CDDP-induced nephrotoxicity has been found to be substantially influenced by both classic and nonclassic RAS axes. Angiotensin II exacerbates renal damage induced by CDDP. Conversely, inhibiting the pressor arm of RAS in males mitigates this damage. However, activation of the renal vasodepressor arm of RAS exacerbates CDDP-induced nephrotoxicity in females. These findings underscore gender differences in renal function and response to RAS-related interventions in the presence of CDDP. This SR provides insights into both beneficial and adverse interventions associated with RAS in the CDDP-induced nephrotoxicity, offering valuable considerations for researchers and clinicians.